(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic can be described as one of these crises, which has been characterized as one of the biggest international public health problems of the last decades, having affected practically the entire planet. Such an event causes psychological and social disturbances that affect the coping capacity of the whole society, at varying levels of intensity and spread. The present study aims to address the perception of the nursing team in the face of the coronavirus pandemic, as well as to present scientific evidence on factors associated with the occupational and psychological impact caused by them on health professionals. The method used in the present research was the bibliographic analysis of the integrative type addressing the theme, being carried out through the virtual health library using as descriptors: Nursing. Coronavirus. Pandemic. Mental health. It was observed with a study that the nursing teams have been acting constantly under psychological pressure, which can cause depression and even anxiety. Through the studies carried out, it is concluded that, in the face of a pandemic such as the one we are experiencing, nursing professionals are part of one of the most affected groups, exposed to emotional pain and the risk of contagion that considerably affects mental health. However, immediate care must be applied, at all levels and by the most different areas of knowledge, in order to reduce even more negative results in the mental health of these professionals.